Traditional uses, nutritional properties, phytochemical metabolites, pharmacological properties, and potential applications of Lilium spp.: a systematic review - Wang, Yi; Chen, Huan; Feng, Pucheng; Wang, Deyun; Du, Xiaoquan (Frontiers in Pharmacology, 2025)
IntroductionLilium spp., perennial bulbous plants native to the Northern Hemisphere, have long been valued in traditional medicine, particularly across Asia. The bulbs of Lilium brownii (“Bai He” in traditional Chinese medicine) have been documented since the Han dynasty as both food and medicine to nourish yin, moisten the lungs, clear heart fire, and calm the spirit—traditionally used for conditions such as depression and diabetes. Contemporary research has increasingly validated these traditional claims, revealing diverse pharmacological activities including antidepressant and antitumor effects.MethodsA comprehensive literature review was conducted using databases including Web of Science, PubMed, ACS Publications, Google Scholar, Baidu Scholar, and CNKI, as well as the Encyclopedia of Life, Flora of China, and Plants of the World Online. Taxa recorded in the Chinese Pharmacopoeia (2025) were included: Lilium lancifolium Thunb., Lilium brownii F. E. Brown var. viridulum Baker, and Lilium pumilum DC, and related species. All relevant multilingual publications were critically evaluated and accurately cited. Chemical structures of isolated metabolites were visualized using ChemDraw v19.0.ResultsLilium spp. are consumed in various culinary and processed forms, including steamed bulbs, flour, wine, and functional beverages. Nutritionally, they are rich in polysaccharides, saponins, dietary fibers, vitamins, amino acids, starch, pectin, phospholipids, and essential minerals such as calcium and iron. To date, 123 chemical metabolites have been isolated and characterized, with saponins, flavonoids, phenylpropanoids, and polysaccharides recognized as the principal bioactive metabolites. Pharmacological studies have demonstrated a wide range of biological activities-anti-inflammatory, antioxidant, antitumor, antidepressant, sedative, hepatoprotective, hypoglycemic, joint-protective, and immunomodulatory-observed in both in vitro and in vivo models.DiscussionLilium spp. represent a valuable traditional medicinal and nutritional resource with promising potential for modern therapeutic and functional applications. Their integration into health products and cosmetics continues to expand; however, clinical validation remains limited. Further well-designed clinical trials are required to confirm the efficacy, safety, and mechanisms of Lilium-derived preparations. This review highlights recent advances to support the continued scientific and industrial development of Lilium as a multifaceted natural resource.